2022
DOI: 10.1039/d2cy01136k
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined, air- and moisture-stable palladium–imidazo[1,5-a]pyridin-3-ylidene complexes: a versatile catalyst platform for cross-coupling reactions by L-shaped NHC ligands

Abstract: We describe the development of [(NHC)Pd(cinnamyl)Cl] complexes of ImPy (ImPy = imidazo[1,5-a]pyridin-3-ylidene) as a versatile class of precatalysts for cross-coupling reactions. These precatalysts feature fast activation to monoligated Pd(0) with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…We were attracted to sterically demanding ImPy (ImPy=imidazo[1,5‐ a ]pyridin‐3‐ylidene) architecture [20–22] . Sterically, this class of ligands is well‐positioned to satisfy the spacial requirements of the Au I /Au III cycle with variable N1/C5 substitution, while, electronically, the presence of a coordinating donor atom at the C5 position offers the hemilabile handle for stabilization of Au I /Au III intermediates [18] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were attracted to sterically demanding ImPy (ImPy=imidazo[1,5‐ a ]pyridin‐3‐ylidene) architecture [20–22] . Sterically, this class of ligands is well‐positioned to satisfy the spacial requirements of the Au I /Au III cycle with variable N1/C5 substitution, while, electronically, the presence of a coordinating donor atom at the C5 position offers the hemilabile handle for stabilization of Au I /Au III intermediates [18] .…”
Section: Resultsmentioning
confidence: 99%
“…We were attracted to sterically demanding ImPy (ImPy = imidazo [1,5-a]pyridin-3-ylidene) architecture. [20][21][22] Sterically, this class of ligands is well-positioned to satisfy the spacial requirements of the Au I /Au III cycle with variable N1/C5 substitution, while, electronically, the presence of a coordinating donor atom at the C5 position offers the ImPyNMe 2 DippAuCl (L4) AgNTf 2 96 [b] [a] 1,3,5-trimethoxybenzene (1.0 equiv), iodobenzene (1.0 equiv), AgX (1.1 equiv), NHCÀ AuÀ Cl (5 mol %), methanol (0.125 M), 80 °C, 16 h.…”
Section: Ligand Design and Reaction Optimizationmentioning
confidence: 99%
“…In addition to serving as precursors for nucleophilic reagents, nitroaromatics also possess unique advantages as electrophilic reagents, drawing attention. [10][11][12][13][14][15][16][17] Employing nitroaromatics instead of halogenated aromatic can circumvent halogenated waste contamination and certain halogenated aromatic compounds are synthesized through multistep reactions, using nitroaromatics as starting materials. 18 In light of the dual roles of nitroaromatics in cross-coupling reactions, we contemplated the introduction of a reducing agent into the Pd/NHC catalytic system previously reported by our group.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serving as precursors for nucleophilic reagents, nitroaromatics also possess unique advantages as electrophilic reagents, drawing attention. 10–17 Employing nitroaromatics instead of halogenated aromatic can circumvent halogenated waste contamination and certain halogenated aromatic compounds are synthesized through multistep reactions, using nitroaromatics as starting materials. 18…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have revealed the effectiveness of N -heterocyclic carbene (NHC) ligands, such as an imidazopyridine-based carbene and a pyridine-fused triazolylidene in cleaving C–NO 2 bonds. While diverse denitrative conversions of nitroarenes, including amination, ,, hydrogenation, intramolecular C–H arylation, and others, , have been reported, metal-catalyzed denitrative cyanation has not been explored.…”
mentioning
confidence: 99%